Diagnóstico organizacional da cooperativa dos produtores de leite da vila bom jardim-cooperlight, dm Pacajá–PA - RIBAS, Roseane Aparecida (Universidade Federal de Santa Maria, 2022)
The objective of this article is to diagnose the organizational system of an agricultural cooperative in the process of formation. For this purpose, the research was carried out in a milk cooperative in the municipality of Pacajá, in the state of Pará. Forms and interviews were used to collect data structured, applied, respectively, to 40 (82%) cooperated and 6 (67%) members of the board. The research is characterized as descriptive, with quantitative and qualitative approach of the data. For the treatment and systematization of the information the Survey Monkey and Microsoft Office Excel programs were used. It was verified that the profile of the cooperative is represented by 90% of men, 55% are over 50 years of age, 65% have more than 10 years as associates, 63% have incomplete elementary education, these cooperate rural area (95%). It was noted that about 40% do not know the status and 70% have no copy of this. The cooperative has several obstacles that can be solved through the realization of planning, permanent training, development of the cooperative spirit and realization of a more participative management.